Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis. Issue 12 (15th June 2022) - Huang, Fei-Bing; Liang, Na; Hussain, Nusrat; Zhou, Xu-Dong; Ismail, Muhammad; Xie, Qing-Ling; Yu, Huang-He; Jian, Yu-Qing; Peng, Cai-Yun; Li, Bin; Liu, Bin; Chen, Sheng-Huang; et al.
Abstract: Five new glycosides including mimenghuasu A and B (1 -2 ), isolinarin (3 ), cyclocitralosides A and B (4–5 ), along with forty-seven known compounds were isolated from the flower buds of Buddleja officinalis . These structures were elucidated by extensive spectroscopic analysis (UV, IR, 1 D, 2 D NMR, and MS spectra). The anti-inflammatory activities of the isolated compounds were determined by enzyme-linked immunosorbent assay (ELISA) on the expression of TNF- α (LPS-activated RAW264.7 cells) and MTT experiment on LPS-induced HUVECs proliferation effects. Good suppressive effects on the expression of TNF- α were shown by 4 and 5 with IC50 values of 19.35 and 22.10 μM, respectively, compared to positive control indomethacin (IC50 16.40 μM). In addition to this, some isolated compounds exhibited excellent antioxidant activities including compounds 16, 18, 29, 39, and 47 (IC50 μM: 82.59, 72.94, 33.65, 46.67, and 20.81, respectively) with almost the same or stronger potency with reference to vitamin C as positive control (IC50 81.83 μM). Graphical Abstract: UF0001